An Analytical Study of RBSK and Women Economic Empowerment in Bulandshahr District of Uttar Pradesh - Kumar, Sanjeev (Journal of Commerce and Trade, 2018)
Women Empowerment is a well known development term in recent era. There are little methods available to measure it and analyse it. Empowerment has intrinsic, extrinsic as well as instrumental value. Apart from this, empowerment can be economic, social or political. In the broader form, empowerment means to delegate the power of freedom in choice and action. Women empowerment delegates more authority and control to women over those resources and decisions that affect their life. Un-empowered women have very limited power to negotiate better for their life in many ways formal or informal, direct or indirect and legal or illegal. There is no direct impact of financial aid covered under the scheme with respect to the selected respondents. But the aspects and areas covered in the scheme do economically support rural women and for their empowerment. Overall the respondents are satisfied with the entire coverage and the facilities provided by Rashtriya Bal Swasthya Karyakram. Classification-JEL : D31, D63, J16, N15